2010
DOI: 10.1093/brain/awq138
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in brain structure and functional connectivity in prescription opioid-dependent patients

Abstract: A dramatic increase in the use and dependence of prescription opioids has occurred within the last 10 years. The consequences of long-term prescription opioid use and dependence on the brain are largely unknown, and any speculation is inferred from heroin and methadone studies. Thus, no data have directly demonstrated the effects of prescription opioid use on brain structure and function in humans. To pursue this issue, we used structural magnetic resonance imaging, diffusion tensor imaging and resting-state f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
254
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(285 citation statements)
references
References 68 publications
25
254
6
Order By: Relevance
“…These support our hypothesis that heroin-dependent and major depression subjects have shared frontal GMV alterations compared to health controls. The present findings also are consistent with other structural and functional neuroimaging studies which found disruptions of the frontal cortex in individuals with repeated drug abuse including heroin-dependence (Upadhyay et al, 2010;Vasic, Walter, Hose & Wolf, 2008;Verdejo-Garcia, Rivas-Perez, Lopez-Torrecillas & Perez-Garcia, 2006). …”
Section: Discussionsupporting
confidence: 92%
“…These support our hypothesis that heroin-dependent and major depression subjects have shared frontal GMV alterations compared to health controls. The present findings also are consistent with other structural and functional neuroimaging studies which found disruptions of the frontal cortex in individuals with repeated drug abuse including heroin-dependence (Upadhyay et al, 2010;Vasic, Walter, Hose & Wolf, 2008;Verdejo-Garcia, Rivas-Perez, Lopez-Torrecillas & Perez-Garcia, 2006). …”
Section: Discussionsupporting
confidence: 92%
“…Emerging evidence implicates the importance of the BLA3 NAc circuit in the opiate addiction process (Frenois et al, 2005;Upadhyay et al, 2010;Xie et al, 2011). Opiate dependence and withdrawal are associated with structural and functional abnormalities in the amygdala of abstinent opiate-dependent patients and disturbed functional connectivity between the amygdala and associated pathways, including the PFC and NAc (Upadhyay et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Opiate dependence and withdrawal are associated with structural and functional abnormalities in the amygdala of abstinent opiate-dependent patients and disturbed functional connectivity between the amygdala and associated pathways, including the PFC and NAc (Upadhyay et al, 2010). Previous reports demonstrate an important role for intra-BLA DA transmission during the processing of drug-related reward learning and relapse-related phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of volume in the amygdala, white matter anisotropy in the afferent and efferent pathways of the amygdala and a decrease in functional connections in the amygdala have been determined in individuals prescribed long-term opioid for therapeutic reasons (14). These findings are clinically important in terms of showing functional changes in regions of the brain associated with motivation and reward functions, impulse control and affect regulation in individuals prescribed long-term opioid.…”
Section: Discussionmentioning
confidence: 99%